Effect of Low Solid/Liquid Ratio on Hydrothermal Synthesis of Hydroxyapatite with Green Template from Banana Flower (Musa acuminata Cavendish) - Ferli Septi Irwansyah; Alfi Ikhlasul Amal; Eko Prabowo Hadisantoso; Atiek Rostika Noviyanti; Diana Rakhmawaty Eddy; Azman Bin Ma'Amor; Risdiana Risdiana (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2023)
Hydroxyapatite (HA) was successfully synthesized using the hydrothermal method. This study aimed to analyze the effect of a low solid/liquid ratio on the properties of HA crystals. HA synthesis was performed using chicken eggshells and the hydrothermal method at a temperature of 150°C. The solvent amount was kept constant, while the solid amount varied (half-reaction). The characteristics of HA were determined using XRD, FTIR, PSA, and SEM. The results showed that the purity and size of HA were influenced by a low solid/liquid ratio, while the crystallinity remained relatively unchanged, directly impacting the lattice parameter value. FTIR analysis revealed the absence of the O-H group in the sample with the low solid/liquid ratio. PSA results showed a smaller particle size of 0.995 µm for the sample with the low solid/liquid ratio. SEM results demonstrated a smaller particle size in the sample with a low solid/liquid ratio when observed at the same magnification